Listeria monocytogenes y la listeriosis, problema de salud pública en México - Gloria Marisol Castañeda-Ruelas; Cristóbal Chaidez-Quiroz; Erika Paloma Salazar-Jiménez; Ulises Hernández-Chiñas; Carlos Alberto Eslava-Campos (Instituto Nacional de Salud Pública, 2018)
[Not available]